Immunologically Reactive Equivalents of Fibrinogen in Sera and Urine of Children with Renal Disease. Issue 251 (February 1972) - Ekert, H.; Barratt, T. M.; Chantler, C.; Turner, M. W.
Abstract : Fibrin degradation products (FDP) were assayed by the tanned red cell haemagglutination inhibition technique in the sera and urine of children with renal disease, and their correlation with other parameters of proteinuria was examined. Urinary FDP were present in greater quantities in subjects with heavy and unselective proteinuria, and were not correlated with serum levels of FDP. FDP may derive from fibrinogen filtered through leaky glomeruli or from intravascular coagulation restricted to the kidney: the data presented are compatible with either hypothesis.